Penyuluhan Anti-Bullying di SDN Citarik: Membangun Karakter Pelajar Pancasila dan Lingkungan Belajar Inklusif - Fauziah, Nisa; Al Fatihah , Aina; Ananda, Amalia; Arrobany, Alfy Awal; Rohandy, Fajar (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
This research discusses a Community Service Program (KKN) in the field of education, specifically a campaign about the dangers of bullying in the school environment. This campaign was implemented as an effort to build the character of the Pancasila Student by creating an inclusive learning environment. The methods used in this campaign include lectures supported by visual media such as PowerPoint and animated videos, along with interactive Q&A sessions, quizzes, and the distribution of educational posters. The results of the campaign show that students were still unfamiliar with bullying. They often engaged in bullying behaviors without realizing it towards their classmates. In conclusion, the campaign made students more aware of the dangers of bullying and the negative impacts on victims. Additionally, this campaign was effective in raising students’ awareness to be more cautious in their words and actions, thus contributing to the development of positive character. By fostering a positive character aligned with the Pancasila Student character, it is hoped that an inclusive learning environment will be achieved. The implications of these results indicate the need for similar campaigns in other schools to strengthen the Pancasila Student character.